A case of mycetoma-like chromoblastomycosis in Qatar. (2020) - Ali, Gawahir A.; Goravey, Wael; Taj-Aldeen, Saad J.; Petkar, Mahir; Al-Bozom, Issam; Hadi, Hamad Abdel
Highlights: Historical background of the disease. Rare and neglected fungal infection. Importance of MDT approach: radiology and histology. Difficult management and need for prolonged follow up. Abstract: Chromoblastomycosis is one of the neglected tropical mycoses associated with chronic infection of the skin and subcutaneous tissues. We report a case of 49-year-old patient originally from India presented with a mycetoma-like lesion in his right foot which was slowly progressing over three-year period. The diagnosis of chromoblastomycosis was confirmed following surgical excision and identification of the unique histological pathology of muriform bodies. The patient was subsequently treated with a prolonged course of oral itraconazole with a favorable outcome. The clinical presentations, assessment and management of the disease are outlined.